Exploring Islamic local wisdom of halal tourism destinations toward return visits ‎and the perception of Islamic socio-cultural responsibility = استكشاف الحكمة المحلية الإسلامية حكمة وجهات السياحة الحلال نحوزيارات العودة وتصورالمسؤولية الاجتماعية والثقافية الإسلامية - Alam, Azhar; Karima, Nida Izzatul; Ab Talib, Mohamed Syazwan; Md Sawari, Siti Salwa (Deanship of Scientific Research (DSR), The University of Jordan, 2026)
Objectives: The purpose of this study is to analyze how Islamic local wisdom and socio-cultural responsibility influence Muslim tourists' decisions to revisit halal destinations.